2015
DOI: 10.1007/s11099-015-0121-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in transport of photosynthates between high-and low-yielding Ipomoea batatas L. varieties

Abstract: Previous studies have focused mainly on the accumulation of photosynthates and less on their distribution in sweet potato (Ipomoea batatas L.). In addition, the effect of photosynthate accumulation in root tubers on photosynthate distribution was not considered. Thus, a field experiment was carried out from May to October (2011 and to clarify the differences in photosynthate transport between high-and low-yielding sweet potato. This study mainly focused on the photosynthetic capacities of leaves, photosynthate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Even high-yielding varieties are easily overgrown due to enhanced soil fertility (Duan et al, 2018), and when overgrowth appears, storage root yields are reduced. Our research group has demonstrated that differences in storage root yield were mainly caused by differences in assimilate unloading in storage roots; this was much more fluent in high-yielding varieties than in low-yielding varieties (Liu et al, 2015a). Our research group has demonstrated that differences in storage root yield were mainly caused by differences in assimilate unloading in storage roots; this was much more fluent in high-yielding varieties than in low-yielding varieties (Liu et al, 2015a).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Even high-yielding varieties are easily overgrown due to enhanced soil fertility (Duan et al, 2018), and when overgrowth appears, storage root yields are reduced. Our research group has demonstrated that differences in storage root yield were mainly caused by differences in assimilate unloading in storage roots; this was much more fluent in high-yielding varieties than in low-yielding varieties (Liu et al, 2015a). Our research group has demonstrated that differences in storage root yield were mainly caused by differences in assimilate unloading in storage roots; this was much more fluent in high-yielding varieties than in low-yielding varieties (Liu et al, 2015a).…”
Section: Discussionmentioning
confidence: 78%
“…Storage root formation is closely related to assimilate transportation from source to sink (storage roots), which is governed by loading of the phloem in source leaf, long-distance transport in the phloem, unloading in sink organs, and metabolism of unloaded sugars in sink cells (Patrick, 1997). Our research group has demonstrated that differences in storage root yield were mainly caused by differences in assimilate unloading in storage roots; this was much more fluent in high-yielding varieties than in low-yielding varieties (Liu et al, 2015a). However, the mechanism of phloem unloading in storage roots of sweetpotato is unclear, likely because of its inconvenience of investigation due to underground organ development.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The leaves and petioles were collected, and stems and storage roots were cut, dried at 60°C in the oven and then ground to a powder using a Waring blender. The powder was analyzed using a stable isotope ratio mass spectrometer (IsoPrime 100, Elementar Analysensysteme GmbH Co. Ltd., Germany) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%